Inserción laboral al servicio público en los Gobiernos Autónomos Descentralizados municipales y su incidencia en el derecho constitucional. - Macías Chamber, Mariana Rosalía (2015)
This legal research thesis entitled: LABOUR MARKET IN THE PUBLIC SERVICE autonomous governments MUNICIPAL AND ITS IMPACT ON THE CONSTITUTIONAL LAW, born of deep research of the problems of Ecuadorians municipal employees from the force of the Constitution and later the Public Service Act, because they establish the obligation of carrying out the merits and opposition contests to fill vacancies obtain in public institutions, but that provision is unnoticed because the Public Service Act does not specify this obligation in municipal autonomous governments. We could while performing this work feel the employment situation of public servants in our province, visiting several cantons we have shown labor policies that affect not only the citizens interested in applying for a position, but also to career civil servants they can not rise within the municipal administration. With the reform of the reform to Chapter 4, Subsystem Recruitment Article 63 of the Law on Public Service article, we will regulate the administrative procedures for admission to public service, giving obligation to comply with the constitutional and legal provisions.